La influencia del marketing relacional en la lealtad de los 4 principales bancos del Perú en Lima Metropolitana - Guerra Angulo, Brenda Yasumi (2022)
The main objective of the investigation is to identify the influence of relationship marketing of the four main banks in Metropolitan Lima on the loyalty of their clients. The relational marketing model presented is based on the one proposed by the authors Morgan and Hunt, which lands on two dimensions: commitment and trust, analyzing how this influence consumer loyalty. The methodology is correlational. For the field work, surveys were applied to a sample of 385 people from 20 to 70 years from the SES. A and B, who reside in Metropolitan Lima and who personally own a product from the four main banks in Peru, in order to identify which aspects of the relationship management of the banks BCP, Interbank, Soctiabank and BBVA Continental influence in the loyalty of its users. The results showed that there is a direct relationship between the variables of relationship marketing and loyalty within the banking sector, thus verifying the hypothesis raised.